Analysis of teaching material needs for metaphorical semantics based on indigenous knowledge from the onang-onang mangupa tradition - Lili Herawati Parapat; Harun Joko Prayitno; Atiqa Sabardila (Global Econedu, 2026)
This study aims to identify the instructional needs for indigenous knowledge-based metaphorical semantics teaching materials in Indonesian higher education. A mixed-methods needs analysis involved 120 students and five lecturers from four Indonesian Language Education Study Programs. Data were collected through questionnaires, semi-structured interviews, and document analysis and analyzed using descriptive statistics and thematic analysis. The results showed that existing materials systematically covered semantic concepts but lacked contextualization and integration of local cultural knowledge. Students and lecturers indicated strong needs for authentic linguistic examples, culturally relevant content, and digitally supported resources. Onang-Onang Mangupa was identified as a potential authentic resource for teaching metaphorical expressions and cultural values. The findings reveal a contextualization gap and provide an empirical foundation for developing culturally responsive metaphorical semantics teaching materials